Antimicrobial resistance in slaughterhouses, Kenya - Hamilton, K.A.; Njoroge, Samuel M.; Momanyi, K.; Murungi, Maurice K.; Odinga, Christian O.; Bor, Nicholas; Ogendo, Allan; Odaba, Josiah; Ogola, Joseph G.; Fèvre, Eric M.; Falzon, Laura C. (Centers for Disease Control and Prevention, 2023)
Slaughterhouses are hotspots for the transmission of antimicrobial-resistant pathogens. We conducted stakeholder discussions on antimicrobial-resistant pathogens within the slaughterhouse setting. Butchers were described as powerful stakeholders; challenges included limited funding and staff, inadequate infrastructure, and limited laboratory capacity. Slaughterhouse workers understood that their work increased their risk for exposure.